Influence of rock salt impurities on limestone aggregate durability - Varner, Jonathan (Kansas State University, 2013)
Some limestone coarse aggregate in concrete pavement can break down under repeated freeze-thaw cycles. Application of rock salt may increase the severity of exposure conditions because of trace compounds, such as calcium sulfate, in rock salt. Subsequently, limestone aggregate in concrete was subjected to freeze-thaw cycling in two methods: salt-treating the aggregate before batching concrete, and half-immersing concrete specimens in rock salt solution during freeze-thaw cycling. Concrete and saw-cut limestone specimens were also subjected to wet-dry cycles in varying salt solutions to examine the influence of trace compounds in rock salt. Freeze-thaw test results indicate that the test methods used were not severe enough to determine if a limestone aggregate was durable or not. The wet-dry testing was also not severe enough to determine the effects of trace compounds in salt solution.
Keywords: Deicing salt impurities; Limestone; Aggregate frost; Durability; Engineering (0537)